2005
DOI: 10.1158/0008-5472.can-05-3016
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Phosphatase and Tensin Homologue Increases Transforming Growth Factor β–Mediated Invasion with Enhanced SMAD3 Transcriptional Activity

Abstract: In normal epithelial tissues, the multifunctional cytokine transforming growth factor-B (TGF-B) acts as a tumor suppressor through growth inhibition and induction of differentiation whereas in advanced cancers, TGF-B promotes tumor progression through induction of tumor invasion, neoangiogenesis, and immunosuppression. The molecular mechanisms through which TGF-B shifts from a tumor suppressor to a tumor enhancer are poorly understood. We now show a role for the tumor suppressor phosphatase and tensin homologu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…Besides Smad7, in the present study, we demonstrated that PTEN was also significantly down-regulated by miR-21 in activated HSCs. PTEN has been implicated in inhib- iting the formation of functional R-Smad complexes (40). In addition, based on the present study, PTEN may also regulate Smad2/3 expression via the PTEN/p-MEK pathway.…”
Section: Discussionsupporting
confidence: 61%
“…Besides Smad7, in the present study, we demonstrated that PTEN was also significantly down-regulated by miR-21 in activated HSCs. PTEN has been implicated in inhib- iting the formation of functional R-Smad complexes (40). In addition, based on the present study, PTEN may also regulate Smad2/3 expression via the PTEN/p-MEK pathway.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with the previous report, we demonstrate that PTEN forms cytoplasmic complexes with Smad2/3. In contrast to HaCaT cells, in which TGF-␤ stimulation promoted formation of such complexes (33), in fibroblasts, TGF-␤ has an opposite effect by dissociating existing complexes. PTEN did not interfere with nuclear translocation of Smad2/3 in either fibroblasts or HaCaT cells, indicating that the inhibition of TGF-␤ signaling by PTEN does not occur through sequestration of Smad2/3 in the cytoplasm.…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies have suggested that PTEN may also play an important role as a negative regulator of the TGF-␤ signaling pathway through direct interaction with Smad2/3. Specifically, PTEN was shown to inhibit TGF-␤-induced motility and invasion of epithelial cells, including the keratinocyte cell line HaCaT and U87MG glioma cells (33). Another group has reported a role for PTEN as a negative regulator of fibrosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…6250) and were used according to the manufacturer's instructions. Confirmatory experiments were performed in IMR-90 cells stably transfected with retrovirus encoding PTEN short hairpin RNA that targets human PTEN (16), resulting in functional abrogation of PTEN activity (Fig. S1).…”
Section: Methodsmentioning
confidence: 99%